2021
DOI: 10.1021/acs.macromol.1c01768
|View full text |Cite
|
Sign up to set email alerts
|

One-Step, Room Temperature Synthesis of Well-Defined, Organo-Soluble Multifunctional Aromatic Polyimides

Abstract: Efficient and ambient synthesis of aromatic polyimides (PIs) from readily available starting materials remains a very challenging task in polymer chemistry. Herein, we report for the first time a robust, one-step synthesis of organo-soluble functional aromatic PIs. Room temperature, metal-free, superacid (TFSA)-catalyzed step polymerization of aryl-terminated diimides with carbonyl compounds (2,2,2-trifluoroacetophenone and indoline-2,3-dione (isatin)) afforded 14 high-molecular-weight, linear, film-forming PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The general synthesis process for PIs is the polycondensation of dianhydride and diamine, in which the performance of PIs is determined by the structure of chosen monomers. , Therefore, rational design of bioderived monomers before polymerization could yield the specific green PIs. Evidence of research results demonstrated that the introduction of aliphatic chains or the trifluoromethyl group (−CF 3 ) contributes to the transmittance of PIs. For instance, PIs prepared from modified monomers such as sorbitol, 4-aminocinnamic acid, and inositol show good performance in terms of transmittance. ,,, Additionally, some researchers disclosed that using monomers containing a benzene ring provide superior thermal stability, such as lignin-based and adenine-based PIs. ,, More recently, the designed monomers containing hydrogen bonding bring additional benefits in PIs, ,,, which with a bio-based content of 17.6% of modified furan-2,5-dicarboxylic acid showed excellent balance in superior physiochemical properties . Tremendous advancements have been achieved in the single performance of bio-based PIs via the above strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general synthesis process for PIs is the polycondensation of dianhydride and diamine, in which the performance of PIs is determined by the structure of chosen monomers. , Therefore, rational design of bioderived monomers before polymerization could yield the specific green PIs. Evidence of research results demonstrated that the introduction of aliphatic chains or the trifluoromethyl group (−CF 3 ) contributes to the transmittance of PIs. For instance, PIs prepared from modified monomers such as sorbitol, 4-aminocinnamic acid, and inositol show good performance in terms of transmittance. ,,, Additionally, some researchers disclosed that using monomers containing a benzene ring provide superior thermal stability, such as lignin-based and adenine-based PIs. ,, More recently, the designed monomers containing hydrogen bonding bring additional benefits in PIs, ,,, which with a bio-based content of 17.6% of modified furan-2,5-dicarboxylic acid showed excellent balance in superior physiochemical properties . Tremendous advancements have been achieved in the single performance of bio-based PIs via the above strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The general synthesis process for PIs is the polycondensation of dianhydride and diamine, in which the performance of PIs is determined by the structure of chosen monomers. 24,25 Therefore, rational design of bioderived monomers before polymerization could yield the specific green PIs. 17−23 Evidence of research results demonstrated that the introduction of aliphatic chains or the trifluoromethyl group (−CF 3 ) contributes to the transmittance of PIs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional polyimide synthesis for soluble poly(ether imides) (PEI) involves a single‐step poly(amic acid) formation and imidization in solution as opposed to the two‐step method typically for all‐aromatic PIs, which requires poly(amic acid) formation in solution with subsequent casting and chemical/thermal cyclodehydration. [ 9–13 ] In sharp contrast, earlier polyamide literature suggested an unconventional route for polyimide synthesis, termed polymerization of monomeric reagents (PMR). PMR employed supramolecular dicarboxylate‐diammonium interactions between aromatic diamines and the dialkylester from an aromatic tetracarboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The number of new molecular sieves discovered every day has been increasing. Examples include: zeolites [1,2], metal-organic frameworks [3][4][5], mesoporous silicas [6], microporous carbons [7], polymers of intrinsic microporosity [8,9], and metal-organic framework with dual functionalities [1,4]. This rapid growth of the available molecular sieves imposes the challenge of understanding the sorption kinetics and equilibrium of a large number of adsorbates of industrial interest.…”
Section: Introductionmentioning
confidence: 99%